2021
DOI: 10.3847/2041-8213/abf7d1
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Solar Wind Turbulence from 0.1 to 1 au during the First Parker Solar Probe–Solar Orbiter Radial Alignment

Abstract: The first radial alignment between Parker Solar Probe and Solar Orbiter spacecraft is used to investigate the evolution of solar wind turbulence in the inner heliosphere. Assuming ballistic propagation, two 1.5 hr intervals are tentatively identified as providing measurements of the same plasma parcels traveling from 0.1 to 1 au. Using magnetic field measurements from both spacecraft, the properties of turbulence in the two intervals are assessed. Magnetic spectral density, flatness, and high-order moment scal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 68 publications
(52 citation statements)
references
References 52 publications
3
49
0
Order By: Relevance
“…Particular attention has been paid to radial alignments between the two probes. Indeed, the first PSP-SO line-up occurred in 2020 September, allowing the radial evolution of solar wind turbulence between 0.1 and 1 au to be studied, i.e., from a highly Alfvénic and less developed turbulence state near the Sun to a fully developed and intermittent turbulence state close to the Earth (Telloni et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Particular attention has been paid to radial alignments between the two probes. Indeed, the first PSP-SO line-up occurred in 2020 September, allowing the radial evolution of solar wind turbulence between 0.1 and 1 au to be studied, i.e., from a highly Alfvénic and less developed turbulence state near the Sun to a fully developed and intermittent turbulence state close to the Earth (Telloni et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Tracing of the cross-helicity evolution with distance from the Sun provided one of the first clear lines of evidence that nonlinear dynamical evolution occurs in the solar wind . More recently (Telloni et al, 2021) measured a stream of solar wind at 0.1 and 1.0 AU and showed that the magnetic spectral density, flatness, and higher order moment scaling laws were consistent with Alfvénic fluctuations near the Sun evolving into fully developed turbulence. Similarly, (Chen et al, 2020) showed that turbulence evolves between 0.17 and 1 AU: at 0.17 AU the data showed increased energy spectral density, a slope of −3/2, lower magnetic compressibility, and increased relative amount of outward propagating Alfvénic fluctuations compared to inward.…”
Section: Turbulent Structuring In the Solar Windmentioning
confidence: 91%
“…This has allowed models of solar wind to be constrained by measurements at different radial distances to the Sun. In particular, the characteristics of MHD turbulence in solar wind are continuously being investigated (e.g., [145][146][147][148][149]), and very recent results show signatures of wave-driven turbulence extending much closer to the Sun [9,[150][151][152].…”
Section: Propagating Wavesmentioning
confidence: 99%